Foundation Sacrifices in Neolithic Houses of the Carpathian Basin - Makkay, Janos (1983)
Published under the direction of Emmanuel Anati. Capo di Ponte (Brescia); p. 160: Vergleich mit babylonischen Bau-Ritualen.